The role of information in self-organization - Pereira, Alfredo [UNESP]; Gonzalez, Maria Eunice Quilici [UNESP] (Taylor & Francis, 2018)
Relations of mutual dependence among the components of a system play a central role in the process of secondary Self-Organization. In the present chapter, we analyze the main principles that characterize the dynamics of such dependency relations, focusing on their informational dimension. Informational relations are distinguished from causal ones, and the organizational dimensions and constitutive sub-processes of such dynamics are identified. Four informational modalities are characterized in the process of secondary Self-Organization: structural, environmental, contextual, and anticipatory. It is argued that the dynamics present in the generation of mutual dependence relations can be expressed in terms of three types of nonlinear processes: cooperative, stationary, and conflictual. From these nonlinear processes, new organizational patterns emerge.